2015
DOI: 10.1097/njh.0000000000000198
|View full text |Cite
|
Sign up to set email alerts
|

Development of End-of-Life Peer Nurse Coaches

Abstract: New nurse hires lacked end-of-life nursing experience in the hospital, and mechanisms were unavailable to guide them. A quality improvement project was developed to address this. Seventy-three registered nurses representing 39 nursing units received training as end-of-life peer nurse coaches. This training included 2 hours of end-of-life education and 2 hours of communication/simulation training. Coaches were provided with communication prompt cards, a Nurse to Nurse: Palliative Care book, and additional resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In summary, timely code status discussions are imperative to honor patients' wishes, decrease suffering and delivery of escalating care, and promote peaceful EOL situations. 19 These results highlight common challenges revolving around the delivery of quality palliative/EOL care to hospitalized patients and their families. This study found that communication issues occurred on many levels, not only between the patient/provider, but between provider services and interprofessional team members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, timely code status discussions are imperative to honor patients' wishes, decrease suffering and delivery of escalating care, and promote peaceful EOL situations. 19 These results highlight common challenges revolving around the delivery of quality palliative/EOL care to hospitalized patients and their families. This study found that communication issues occurred on many levels, not only between the patient/provider, but between provider services and interprofessional team members.…”
Section: Discussionmentioning
confidence: 99%
“…Health-care professionals inherently may not have expertise in communicating with patients and families at end of life and can be effectively coached and educated in order to best facilitate and meet patient/family needs. 7,8,[16][17][18][19] The facilitation of seamless transitions of care when goals changed from curative to comfort was often identified, recognizing the importance of implementing supportive interventions that convey empathy and compassion. One respondent described the situation of a patient who transitioned to comfort care and discussed how staff provided an additional patient room to allow more space for an abundant number of family members to grieve and have private time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This person needs family support and care, as their human needs may gradually increase and be severely affected. 19 Consequences: EOLC leads to an increase in QOL and a reduction in moral distress, emotional exhaustion, a decrease in psychological and social stress, imposing lower costs on the family and the health system.…”
Section: Identifying Antecedents and Consequencesmentioning
confidence: 99%